Cauchy Means of the Popoviciu Type. (4th February 2009) - Anwar, Matloob; Latif, Naveed; Pečarić, J.
Abstract : We discuss log-convexity for the differences of the Popoviciu inequalities and introduce some mean value theorems and related results. Also we give the Cauchy means of the Popoviciu type and we show that these means are monotonic.